Neck and shoulder pain in students: Unveiling associated factors of video display terminal devices use - Saadia Maqbool; Iram Manzoor; Muhammad Talha Sohail; Muhammad Rehan Ramzan; Muhammad Ibtesam; Muhammad Usama (Journal of Shalamar Medical & Dental College)
Background: Neck and shoulder pain is becoming a major public health concern due to increased use of digital display terminal devices. It negatively affects individual’s health and results in a burden on health care system.